Translation of Phraseological Units with the Participation of the Verb "Prendre" (Eurasian Journal of Learning and Academic Teaching, 2022)
French phraseology has a special significance as an object of linguistic research with its unique vocabulary structure and charm. Of particular note is the ability to express multiple meanings using a single word or phrase. This article is devoted to the study of the translational features of phrases involving the verb “faire”.